In Situ Analysis of NMC∣graphite Li-Ion Batteries by Means of Complementary Electrochemical Methods. Issue 9 (29th April 2020) - Landa-Medrano, Imanol; Eguia-Barrio, Aitor; Sananes-Israel, Susan; Lijó-Pando, Silvia; Boyano, Iker; Alcaide, Francisco; Urdampilleta, Idoia; de Meatza, Iratxe
Abstract : Lithium-ion technology is considered as outstanding candidate for implementation in high energy density applications. Adjusting the cycling conditions of electrodes and monitoring the undergoing reactions are necessary to maximize their potentiality and ensure high performance and safe operation for end-users. Herein, in situ electrochemical impedance spectroscopy (EIS), direct current (DC) resistance and differential voltage analysis (DVA) are complementarily used to understand and predict the lifetime of LiNi0.6 Mn0.2 Co0.2 O2 (NMC622) vs graphite coin cells cycled at different upper cut-off voltage (UCV). Lithium de/intercalation reactions in graphite, phase transitions in NMC and the formation of electrode-electrolyte interphases have been identified by DVA. Combined with EIS and DC resistance, the occurrence of these reactions has been monitored upon cycling. The main findings indicate that despite observing other detrimental phenomena (charge transfer resistance increase or irreversibility of NMC622 phase transitions), the different solid electrolyte interphase (SEI) formation and resistance with UCV are most relevant factors affecting cycle life. The loss of lithium inventory is the main cause of the capacity fade. The need of a stable SEI to delay the continuous electrolyte consumption is highlighted. The combined information provided by these techniques can be leveraged by battery management systems to optimize cell performance while cycling.